Some causal aspects in the decrease of function of the aging heart - Ahmad Muhammad Djoyosugito, Ahmad Muhammad Djoyosugito (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1983)
The process of aging of an individual has begun since his existence in the womb. Old age forms the last stage of the process.In this aging process changes take place continuously affecting the morphology and function of the individual, his systems, and organs down to the ultrastructure and biochemical reactions, probably due to "intrinsic mutation"; some of those changes are universal and some are specifically affecting certain organ, tissue or cells.In the aging process the heart is not free from these change characteristics which affect the structure of the heart muscle and the vascular wall, and also their biochemistry. All these changes have their impact on the cardiac function.In old age differences are found in the heart from its previous stages of the aging process, which among others are:1. fragmentation of some myofibrils down to complete degeneration with its specific characteristics,2. decrease of the number of mitochondria: some mitochondria show signs of degeneration, 3. heart perfusion decreases down to 80%,4, degeneration of the coronary vessels.5. a change of noradrenalin metabolism so that in the heart muscle it remains 75%,6. degenerative changes of the cardiac valves.All these changes tend to decrease the function of the heart.Key Words: aging process - "intrinsic mutation" - aging heart - myocardium degeneration - senescence